2018
DOI: 10.1002/nbm.4034
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of normal cadaveric Achilles tendon and enthesis with ultrashort echo time (UTE) magnetic resonance imaging and indentation testing

Abstract: Entheses are regions where tendons and ligaments attach to bone, and are the primary target in seronegative and other diseases of the musculoskeletal (MSK) system. MRI has been widely used for visualizing features of inflammatory and degenerative MSK disease; however, normal tendons and entheses have short transverse relaxation times (T2), and show little or no signal with conventional clinical MRI pulse sequences, making it difficult to investigate their MR properties. In this study we examined the normal MR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 27 publications
2
31
0
Order By: Relevance
“…The authors stressed the utility of this sequence in morphological and quantitative evaluation of enthesitis in PsA patients (79). The same group recently explored the MRI morphology of Achilles tendons and entheses using high resolution MRI UTE sequences, and described its utility as biomarkers of biomechanical degradation of entheses in SpA (80).…”
Section: Recent Advances In the Field Of Mri Enthesitis In Spamentioning
confidence: 99%
See 1 more Smart Citation
“…The authors stressed the utility of this sequence in morphological and quantitative evaluation of enthesitis in PsA patients (79). The same group recently explored the MRI morphology of Achilles tendons and entheses using high resolution MRI UTE sequences, and described its utility as biomarkers of biomechanical degradation of entheses in SpA (80).…”
Section: Recent Advances In the Field Of Mri Enthesitis In Spamentioning
confidence: 99%
“…(a,b) Courtesy of Professor Iris Eshed, Sackler School of Medicine, Tel Aviv University, Tel Aviv, Israel. (c,d) have been taken from the OMERACT MRI heel enthesitis exercises(27,80).…”
mentioning
confidence: 99%
“…Ultrashort echo time (UTE) sequences with echo times <100 µs can detect fast decaying signals and provide a much higher signal to noise ratio for short T 2 tissues than conventional clinical gradient recalled echo–type sequences with much longer echo times . In the past decade, these UTE sequences have been widely investigated for both morphological and quantitative imaging of short T 2 tissues, including calcified cartilage, menisci, tendons, ligaments, bone, and myelin …”
Section: Introductionmentioning
confidence: 99%
“…1 In the past decade, these UTE sequences have been widely investigated for both morphological and quantitative imaging of short T 2 tissues, including calcified cartilage, menisci, tendons, ligaments, bone, and myelin. [2][3][4][5][6][7] Fat suppression is very important for UTE imaging of musculoskeletal tissues. [8][9][10] This is because UTE imaging tends to show a high fat signal, attributed to fat's high proton density and short T 1 value, which lead to low contrast for short T 2 tissues.…”
Section: Introductionmentioning
confidence: 99%
“…42 UTE-T2* values have been shown to be sensitive to these biochemical collagen matrix changes. [6][7][8]38 Moreover, this technique has been used by several scholars to assess the biochemical healing process of short T2 tissue. 3,10,30 For instance, Biercevicz et al 3 reported that UTE-T2* values were significantly associated with structural properties as determined by tensile testing regarding the healing of the anterior cruciate ligament.…”
mentioning
confidence: 99%